Pro Nagios 2.0 - Turnbull, James (Apress, 2012)
This is a common scenario in the IT industry. IT staff are geographically and temporally separated from the systems and applications they manage. All troubleshooting, monitoring, and management of systems and applications occurs remotely. The systems and applications being managed are complex and hugely configurable. They are also made up of multiple components— hardware, software, networking devices, networks, and supporting infrastructure like environmental and electrical systems. In the event of a problem, many of these components need to be checked in order to eliminate them as a cause.